In Vitro Callus formation and propagation from embryonic axes of two cultivars of Soybean - Al Awad, Daniel (Latakia University Journal -Biological Sciences Series, 2013)
The objective of this research isto study the in vitro effect of some plant hormones (growth regulators) BAP,NAA, 2,4-D, and genotype on callus and bud formation from embryonic axes of two Soybean cultivar seeds (sb-44, sb-172). The embryonic axes were cultured on MS basal medium and MS supplemented with 1, 2, 3 mg/l BAP alone and in combination with 0.5 mg/l NAA.The cultures were maintained at 25 C˚±1 with photoperiod of 16 hours light (2000-2500 lux) and 8 hours dark.The highest percentage92.5% and mean average 4.63 of callus formation were recorded on MS medium containing BAP (3 mg/l) and NAA (0.5 mg/l). The highest percentage 67.5% and average 3.38 of buds formation were obtained on MS medium supplemented 1 mg/l BAP and 0.5 mg/l NAA in cultivar sb-44. The percentage of callus formation increased, while the percentage of bud formation decreased with each increase in BAP concentration when used alone. A positive increase was observed in all mediums in the combination of 0.5 mg/l NAA or 0.5 mg/l 2. 4-D in the two cultivars used in this study. This study showed the genotypic difference effect on callus and bud formation.Roots were formed from allplantlets cultured on MS medium without plant hormones.Rooted plantlets were transferred into pots with nutrient soil, irrigated with water, and adapted tolaboratory conditions. Good plants grown to maturity were obtained in 12-13 weeks.